Inhibition of Endosomal Transport Results in Decreased Synthesis of Nucleocapsid Protein of PHV Virus - M. Muyangwa; E.E. Garanina (Учёные записки Казанского университета: Серия Естественные науки)
This paper is devoted to investigation of molecular mechanisms of transport of nucleocapsid protein of non-pathogenic virus Prospect Hill. Prospect Hill virus (PHV) belongs to the family Bunyaviridae, genus Hantavirus. Hantaviruses utilize the intracellular trafficking pathways for delivery of viral RNA and proteins to the site of viral assembly. While significant progress has been achieved in understanding PHV replication, the role of intracellular transport in virus replication remains largely unknown. Co-localization of PHV nucleocapsid protein and Rab5, Rab7, and Rab11 (early, late, and recycling endosomes, respectively) has been demonstrated using immunofluorescence assay. Western blot analysis has revealed decreased accumulation of nucleocapsid protein when dominant negative (DN) mutant protein forms Rab5 and Rab11were expressed in PHV infected cells. Our data suggest that the functional activity of early, late, and recycling endosomes is essential for replication of HPV proteins. The obtained results are of great importance for comprehension of molecular and cellular mechanisms of pathogenesis of hantaviral infection.